Development of Digital-Based Teaching Materials (Flipbooks) as an Effort to Help Students Learn Service and Smash Skills in Sepak Takraw - I Nyoman Suardana; I Ketut Semarayasa; I Wayan Muliarta; Luh Putu Tuti Ariani (Universitas Negeri Semarang, 2025)
This research is based on observations conducted through Google Forms and interviews showing that 97.6% of respondents stated the need for effective and flexible learning innovations. In addition, 100% of respondents stated that flipbook-based digital learning materials have never been used in basic sepak takraw learning techniques. Based on the results of the needs analysis, this study aims to develop flipbook digital teaching materials related to basic service techniques and sepak takraw smash materials. This study applies the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The data analysis techniques used are descriptive quantitative and qualitative. The subjects of this study were fifth-semester students of the physical education, health, and recreation study program with a purposive sample. The final results show that the content/material expert test is in the very feasible category (100%), the design expert test is in the feasible category (88.3%), the media expert test is in the very feasible category (96.7%), and the field practitioner test is in the very feasible category (96.9%). Furthermore, the product trial obtained individual test results of 94.2%, small group test of 95.5%, and large group test of 92.7%, all of which are in the very appropriate category. Thus, this flipbook learning material is considered relevant and appropriate for use in sepak takraw learning, and is expected to contribute to the Physical Education, Health, and Recreation Study Program, Faculty of Sports and Health, Ganesha University of Education, and sports practitioners in Indonesia.